2020
DOI: 10.1371/journal.pone.0242211
|View full text |Cite|
|
Sign up to set email alerts
|

Ikaros antagonizes DNA binding by STAT5 in pre-B cells

Abstract: The IKZF1 gene, which encodes the Ikaros transcription factor, is frequently deleted or mutated in patients with B-cell precursor acute lymphoblastic leukemias that express oncogenes, like BCR-ABL, which activate the JAK-STAT5 pathway. Ikaros functionally antagonizes the transcriptional programs downstream of IL-7/STAT5 during B cell development, as well as STAT5 activity in leukemic cells. However, the mechanisms by which Ikaros interferes with STAT5 function is unknown. We studied the genomic distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…3f, g , dashed boxes). These findings were consistent with previous studies suggesting that Ikaros engages in antagonism with STAT5 in lymphoid populations, and suggested that Aiolos may engage in a similar mechanism to regulate effector CD4 + T subset programming 44 , 45 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3f, g , dashed boxes). These findings were consistent with previous studies suggesting that Ikaros engages in antagonism with STAT5 in lymphoid populations, and suggested that Aiolos may engage in a similar mechanism to regulate effector CD4 + T subset programming 44 , 45 .…”
Section: Resultssupporting
confidence: 92%
“…Thus, the overlapping motifs we observe are also suggestive of potential Aiolos or Aiolos/STAT3 antagonism with STAT5. These findings are consistent with several recent studies suggesting that a related family member, Ikaros, which shares the core IkZF DNA binding motif, engages in antagonism with STAT5 in both normal B cell development and leukemic settings 44,45 . Ultimately, further work is needed to establish whether the predominant role of Aiolos is to repress IL-2R subunit expression to alter STAT5 activity, or whether Aiolos-possibly in cooperation with STAT3-functions to antagonize STAT5 binding more broadly.…”
Section: Discussionsupporting
confidence: 93%
“…We show that Ikaros is required at the fraction C' stage of B1 cell differentiation as observed for B2 progenitors, suggesting similar regulation of gene expression, particularly in antagonizing genes regulated by IL-7/STAT5. 8 Our results also suggest that Ikaros functions as a tumor suppressor by repressing STAT5 activity in B cell progenitors of fetal and adult origin. Whether the B1 cell equivalent exists in humans is still unclear.…”
supporting
confidence: 59%
“…As Ikaros antagonizes STAT5 binding to DNA in pre-B2 cells, we asked if Ikaros has a similar function in B1 progenitors. 8 GSEA of STAT5-induced genes antagonized by Ikaros in pre-B2 cells revealed their enrichment among the upregulated genes in Ikaros deficient B1 cells, suggesting that Ikaros also antagonizes STAT5 gene activation in B1 progenitors.…”
mentioning
confidence: 99%
“…IKAROS, a hematopoietic-specific transcription factor encoded by IKZF1 (Ikaros family zinc finger 1), is a central regulator of hematopoiesis (Table 1). [55][56][57][58][59][60][61] In humans, somatic IKZF1 mutations-mainly deletions-were originally associated with B-ALL in children and adults with poor prognosis. [62][63][64] Currently, a range of germline IKZF1 disease-causing mutations have been identified in patients with diverse clinical phenotypes; however, a unifying feature is B-cell lymphopenia resulting from different molecular mechanisms that disrupt early B-cell development.…”
Section: Ikarosmentioning
confidence: 99%